Three Years of High-contrast Imaging of the PDS 70 b and c Exoplanets at Hα with MagAO-X: Evidence of Strong Protoplanet Hα Variability and Circumplanetary Dust - Laird M. Close; Jared R. Males; Jialin Li; Sebastiaan Y. Haffert; Joseph D. Long; Alexander D. Hedglen; Alycia J. Weinberger; Katherine B. Follette; Daniel Apai; Rene Doyon; Warren Foster; Victor Gasho; et al. (The Astronomical Journal)
We present 3 yr of high-contrast imaging of the PDS 70 b and c accreting protoplanets with the new extreme AO system MagAO-X as part of the MaxProtoPlanetS survey of H α protoplanets. In 2023 and 2024, our sharp (25–27 mas FWHM), well-AO-corrected (20%–26% Strehl), deep (2–3.6 hr) images detected compact ( r ∼ 30 mas; r ∼ 3 au) circumplanetary disks (CPDs) surrounding both protoplanets. Starlight scattering off the front edge of these dusty CPDs is the likely source of the bright compact continuum light detected within ∼30 mas of both planets in our simultaneously obtained continuum 668 nm filter images. After subtraction of contaminating continuum and point-spread function residuals with pyKLIP angular differential imaging and spectral differential imaging, we obtained high-contrast ASDI H α images of both planets in 2022, 2023, and 2024. We find the H α line flux of planet b fell by (8.1 ± 1.6) × 10 ^−16 erg s ^−1 cm ^−2 , a factor of 4.6 drop in flux from 2022 to 2023. In 2024 March, planet b continued to be faint with just a slight 1.6× rise to an H α line flux of (3.64 ± 0.87) × 10 ^−16 erg s ^−1 cm ^−2 . For c, we measure a significant increase of (2.74 ± 0.51) × 10 ^−16 erg s ^−1 cm ^−2 from 2023 to 2024, which is a factor of 2.3 increase. So both protoplanets have recently experienced significant H α variability with ∼1 yr sampling. In 2024, planet c is brighter than b: as c is brightening and b generally fading. We also tentatively detect one new point source “CC3” inside the inner disk (∼49 mas; at PA ∼ 295°; 2024) with orbital motion roughly consistent with a ∼5.6 au orbit.